ANALYSIS OF MURABAHAH FINANCING IN THE APPLICATION OF FINANCING SERVICES PRODUCTS IN SHARIA BANKING - Heru Kuswandito; Muhamad Riwan (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2019)
The research theme is the concept of a bank in accordance with Islamic economics. The purpose of the study was to analyze murabaha financing in Islamic banking. Research is a literature study. The object of research is the banking industry in Indonesia. To ensure that the implementation of murabahah financing is in accordance with this concept, it requires strict supervision of the Sharia Supervisory Board or the National Islamic Council, so that murabahah as sharia banking financing can be maintained and does not tarnish the image and prestige of Islamic banking so that there is no impression that Islamic banks are the same as conventional banks.